Single or Multiple Porosity Cut Off A New Relevance Provided By Application of A New Approach - Bambang Widarsono (Testing Center for Oil and Gas LEMIGAS, 2010)
Porosity cut-off is one of the most important parameter normally used to differentiatebetween reservoir and non-reservoir rocks. Quantity of the parameter certainly dictatesreservoir volumes, hence directly influences economics and commerciality of a given oil/gas field. An ever critical issue in relation to this parameter is whether the use of porositycut-off has to be established through a single or multiple values especially for heterogeneousformation rocks. This certainly may lead to different reservoir sizes along with thetechnical and economical consequences. The study presented in this article is meant to furtherinvestigate this question. The thrust of this study lies on the application of a newlyproposed method for determining porosity cut-off. It is put that with this new and reliablemethod – compared to the traditionally used method – a more conclusive answer can beachieved. For the purpose, a heterogeneous limestone reservoir in West Java – Indonesiais used. Evaluation, analysis, and application of the new method on data from the field’seight wells have shown that multiple porosity cut-off values are needed for better definitionsof reservoirs. Application of a single value for these reservoirs can still be regardedas unrepresentative. The fact underlines that – despite the new approach’s reliability –heterogeneity governs more over the use of either single or multiple cut-off values ratherthan limitations of method. The study also proves that the new method for determiningporosity cut-off works well for highly heterogeneous reservoir rocks.